Improving perioperative brain health: an expert consensus review of key actions for the perioperative care team. (February 2021) - Peden, Carol J.; Miller, Thomas R.; Deiner, Stacie G.; Eckenhoff, Roderic G.; Fleisher, Lee A.; ,; Fleisher, Lee; Deiner, Stacie; Eckenhoff, Roderic; Peden, Carol; Brown, I.V.; Charles, H.; et al.
Summary: Delirium and postoperative neurocognitive disorder are the commonest perioperative complications in patients more than 65 yr of age. However, data suggest that we often fail to screen patients for preoperative cognitive impairment, to warn patients and families of risk, and to take preventive measures to reduce the incidence of perioperative neurocognitive disorders. As part of the American Society of Anesthesiologists (ASA) Perioperative Brain Health Initiative, an international group of experts was invited to review published best practice statements and guidelines. The expert group aimed to achieve consensus on a small number of practical recommendations that could be implemented by anaesthetists and their partners to reduce the incidence of perioperative neurocognitive disorders. Six statements were selected based not only on the strength of the evidence, but also on the potential for impact and the feasibility of widespread implementation. The actions focus on education, cognitive and delirium screening, non-pharmacologic interventions, pain control, and avoidance of antipsychotics. Strategies for effective implementation are discussed. Anaesthetists should be key members of multidisciplinary perioperative care teams to implement these recommendations.